Pengembangan Flash Flipbook sebagai Media Pembelajaran pada Submateri Peranan Jamur di Kelas X SMA - Nury Kamelia; Laili Fitri Yeni; Wolly Candramila (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This study aims to develop a flash flipbook as learning media followed by testing its validity and reliability. The development model used is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) which is focused on the first 3 stages, namely Analyze, Design, and Development. Validation activities include instrument validation by 2 validators using the Guttman scale and media validation by 5 validators with 4 rating scales based on the Likert scale. Validation is done by filling out a closed questionnaire. Flash flipbook media validation assesses 3 aspects, namely aspects of format, content, and language. Analysis of the results of the flash flipbook validation using the Aiken's V method and the reliability test using the ICC (Intraclass Correlation Coefficient). This study shows that the validation results with the Aiken standard of 0.87 with 1 improvement and the ICC reliability results are 0.985 in the very good category. The addition of the literatures with the latest issue can increase the feasibility of this media. This flash flipbook can provide good visualization for students so as to provide variety in learning activities.